2016
DOI: 10.1080/10408444.2016.1214677
|View full text |Cite|
|
Sign up to set email alerts
|

A review of the carcinogenic potential of glyphosate by four independent expert panels and comparison to the IARC assessment

Abstract: The International Agency for Research on Cancer (IARC) published a monograph in 2015 concluding that glyphosate is "probably carcinogenic to humans" (Group 2A) based on limited evidence in humans and sufficient evidence in experimental animals. It was also concluded that there was strong evidence of genotoxicity and oxidative stress. Four Expert Panels have been convened for the purpose of conducting a detailed critique of the evidence in light of IARC's assessment and to review all relevant information pertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 61 publications
(70 reference statements)
1
48
0
5
Order By: Relevance
“…Among environmental factors, glyphosate or its formulated products have been indicated to be linked with increased incidence of and mortality by multiple diseases (including cataract related to subsequent breast carcinoma) and cancer (Swanson et al, 2014;Singh et al, 2017). In the latter category, associations were found with non-Hodgkin lymphoma or multiple myeloma incidence (Hardell and Eriksson, 1999;McDuffie et al, 2001;Hardell et al, 2002;De Roos et al, 2003Eriksson et al, 2008;Schinasi and Leon, 2014;Mesnage et al, 2015b), although other reviews claimed no causal relationship between exposure to glyphosate and lymphohematopoietic cancers (Acquavella et al, 2016;Chang and Delzell, 2016;Williams et al, 2016a). Some of these findings have been questioned by Monsanto (Acquavella et al, 1999) and a recent cohort prospective epidemiology study carried out in the US on 57310 licensed pesticide applicators and 32347 spouses in Iowa or North Carolina States found no apparent correlation between glyphosate use and solid tumor or lymphoid malignancies, including non-Hodgkin lymphoma, except for increased risk of acute myeloid leukemia in case of high exposure (Andreotti et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…Among environmental factors, glyphosate or its formulated products have been indicated to be linked with increased incidence of and mortality by multiple diseases (including cataract related to subsequent breast carcinoma) and cancer (Swanson et al, 2014;Singh et al, 2017). In the latter category, associations were found with non-Hodgkin lymphoma or multiple myeloma incidence (Hardell and Eriksson, 1999;McDuffie et al, 2001;Hardell et al, 2002;De Roos et al, 2003Eriksson et al, 2008;Schinasi and Leon, 2014;Mesnage et al, 2015b), although other reviews claimed no causal relationship between exposure to glyphosate and lymphohematopoietic cancers (Acquavella et al, 2016;Chang and Delzell, 2016;Williams et al, 2016a). Some of these findings have been questioned by Monsanto (Acquavella et al, 1999) and a recent cohort prospective epidemiology study carried out in the US on 57310 licensed pesticide applicators and 32347 spouses in Iowa or North Carolina States found no apparent correlation between glyphosate use and solid tumor or lymphoid malignancies, including non-Hodgkin lymphoma, except for increased risk of acute myeloid leukemia in case of high exposure (Andreotti et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…Furthermore, the experts argued that, by analyzing the data available until before the publication of the IARC, there was no such document that would allow the Agency to change the conclusions on the carcinogenicity of the glyphosate disclosed up to that time. The conclusions of the research clearly stated that glyphosate did not pose any risk to humans [54,55].…”
mentioning
confidence: 81%
“…The company stated that, from the results obtained, it was evident that, despite the worst conditions of exposure, there was no risk associated with exposure through the normal use of the product in agriculture or to manage weeds along roadsides or in domestic and industrial areas [54][55][56][57].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The health issue was reignited in 2015 when the International Agency for Research on Cancer (IARC) published a monograph concluding that glyphosate is ‘probably carcinogenic to humans’ . The US Environmental Protection Agency and others have since concluded that glyphosate is likely not a carcinogen, but the firestorm over its safety continues in both popular press and scientific publications . In addition, concerns are often raised about the safety of glyphosate formulations that contain the original tallow amine ethoxylate ‘Roundup surfactant.’ This surfactant type has known aquatic and eye toxicity issues that are commonly addressed with mandatory application restrictions and requirements for operators to wear personal protective equipment (PPE).…”
Section: Future For Glyphosate and Glyphosate Cropsmentioning
confidence: 99%